Implementation of Inmate Classification: An Empirical Study at Class IIA Correctional Facility Banda Aceh - Nasrizal, Nasrizal (LOCUS MEDIA PUBLISHING, 2025)
This study examines the implementation of inmate classification at the Banda Aceh Class II A Correctional Facility, highlighting its significance as a core component of the Indonesian correctional system. Inmate classification serves as both a security mechanism and a rehabilitative strategy, ensuring that prisoners are grouped according to specific criteria such as criminal background, age, gender, and length of sentence. By doing so, correctional institutions are expected to maintain order while also providing more tailored rehabilitation and reintegration programs. Empirical findings, however, reveal that the practice of classification in Banda Aceh has not been fully aligned with regulatory standards. Structural constraints such as overcrowding, insufficient infrastructure, and limited human resources have hindered the ability of the institution to enforce strict separation among inmates. In many cases, the lack of adequate facilities and specialized personnel has led to inconsistencies between the normative framework and the actual implementation of classification. These gaps highlight the tension between the legal mandate of correctional law and the practical realities faced by correctional institutions in Indonesia. The study concludes that while inmate classification has been applied in principle, its effectiveness remains limited due to systemic and institutional challenges. Strengthening institutional capacity, improving coordination, and enhancing staff training are critical to achieving a classification system that fulfills its intended role. Such reforms are essential not only for maintaining security but also for ensuring the protection of human dignity and the realization of a correctional system that genuinely promotes rehabilitation and reintegration.